2008
DOI: 10.1136/jech.2006.058628
|View full text |Cite
|
Sign up to set email alerts
|

Tackling inequalities in health: evaluating the New Deal for Communities initiative

Abstract: Evidence from two-year follow-up does not support an NDC effect, either overall or for particular population groups. Residents with lower education experienced the least favourable health profiles at baseline and the smallest improvements. Programme leaders should consider how to encourage participation among those with the lowest education. A shallower social gradient in participation in education and training in NDC areas and a lack of gradient in income, crime and environmental outcomes indicate that some a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 16 publications
2
45
1
1
Order By: Relevance
“…The likelihood of quitting smoking, finding work and participating in education or training, for example, increased steadily with increasing levels of education and the likelihood of developing a new long-term limiting illness decreased with increasing levels of education. 68 Similar differential impacts were found by gender, age and ethnicity and these patterns were mirrored in comparator areas. There were, however, two important exceptions, suggesting that at least some of the social inequalities that drive health inequalities were growing less fast in NDC areas than in comparator areas during these early years of the programme.…”
Section: Previous Research On the Impact Of The New Deal For Communitsupporting
confidence: 62%
See 2 more Smart Citations
“…The likelihood of quitting smoking, finding work and participating in education or training, for example, increased steadily with increasing levels of education and the likelihood of developing a new long-term limiting illness decreased with increasing levels of education. 68 Similar differential impacts were found by gender, age and ethnicity and these patterns were mirrored in comparator areas. There were, however, two important exceptions, suggesting that at least some of the social inequalities that drive health inequalities were growing less fast in NDC areas than in comparator areas during these early years of the programme.…”
Section: Previous Research On the Impact Of The New Deal For Communitsupporting
confidence: 62%
“…In other words, although this early evidence suggested that things were improving across all domains, it did not support a greater improvement in NDC areas than in non-intervention areas at the 2-year follow-up. 68 Results from the NET published in 2010 present a more positive picture, with a modest effect of the initiative as a whole for the first 8 years of the programme. 69 However, using 2008 data only, only nine of the 36 selected indicators across the six NDC outcome domains (housing and the environment, crime, education, employment, community and health) showed any significant positive difference between NDC and comparator areas.…”
Section: Previous Research On the Impact Of The New Deal For Communitmentioning
confidence: 99%
See 1 more Smart Citation
“…As Stafford et al (2008) argue, those individuals with more financial and human capital are likely to be at an advantage in terms of accessing information, using services and feeding back on their experiences relating to the labour market. There is a need, therefore, to equalise the routes into employability interventions and, perhaps more importantly, to provide tailored support for individuals facing multiple barriers to employment.…”
Section: Need For Individualised Supportmentioning
confidence: 99%
“…Municipal governments are strategically positioned to impact Social Determinants of Health (SDOH), and can therefore act to ameliorate or exacerbate health gradients across neighbourhoods (CSDH, 2008;Stafford et al, 2008). Communities also play a key role in reducing health inequities as they can inform strategies by offering critical insights on local assets and challenges (Bradford, 2005;Hancock, 2009).…”
Section: Introductionmentioning
confidence: 98%